Socio-economic characterization, identification and prioritization of major constraints in Dhumuga learning watershed, Ambo, Ethiopia - Soboka, Diriba Megersa; Dibaba, Regasa (Frontiers in Sustainable Resource Management, 2024)
Understanding the socioeconomic profile of a particular watershed is essential for effective project planning prior to intervention. This study aimed to gather baseline information, record the existing socioeconomic conditions, and identify key constraints within the Dhumuga learning watershed located in the West Shewa zone of Ethiopia. The information was collected through a household survey and focus group discussions. Through focused group discussions, issues like deforestation, water erosion, restricted access to enhanced crop varieties, insufficient irrigation water, and the decline in soil fertility were recognized and prioritized. The survey findings revealed that 82% of households were headed by males, with 40% of household heads possessing basic literacy skills (able to read and write), while 54% were enrolled in primary school (Grades 1–8). Crop production generated 912.08 USD per household per year on average as of 2023 Ethiopian foreign exchange rates to USD, while livestock production generated 2,612.39 US dollar per household per year. In relation to food security, 36% of households have occasionally faced food shortages caused by natural issues during the kiremt season. The research also highlighted challenges such as land degradation from water erosion (46%), improper tillage practices (34%), and deforestation (20%). Additionally, 78% of households rely on firewood for cooking, with 98% of this firewood sourced from local forests and trees, posing a significant threat to forest resources and their sustainable management. For effective management and oversight of the Dhumuga learning watershed, it is recommended to implement forest resource conservation initiatives, promote the use of energy-efficient stoves, enhance soil fertility strategies, establish soil erosion control methods, and introduce innovations for community livelihood improvement, along with raising awareness about various natural resource management activities.